2001
DOI: 10.1021/bp010019l
|View full text |Cite
|
Sign up to set email alerts
|

Carbon Dioxide Induced Soybean Protein Precipitation: Protein Fractionation, Particle Aggregation, and Continuous Operation

Abstract: A novel protein fractionation technique using a volatile electrolyte has been developed. Carbon dioxide was used to isoelectrically precipitate 80% and 95% pure glycinin and beta-conglycinin fractions from soybean isolate. The protein fractions precipitated as primary particles 0.2-0.3 microm in diameter, which under optimum conditions may be recovered as aggregates up to 500 microm in diameter. The dependency of protein fractionation efficiency on aggregate settling rates has been demonstrated. The isoelectri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
21
0

Year Published

2004
2004
2016
2016

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(25 citation statements)
references
References 28 publications
1
21
0
Order By: Relevance
“…The titration curves based on the amino acid sequences were calculated using the software available on the Université de Provence web site (www.up.univ-mrs.fr). The experimental titration data for glycinin were taken from (Thiering et al, 2001a). The theoretical titration curves for glycinin subunits, experimental titration curve for glycinin and isoelectric points of CR lipase isoenzymes are shown in Figure 3.…”
Section: Lipase and Glycinin Interactionmentioning
confidence: 99%
“…The titration curves based on the amino acid sequences were calculated using the software available on the Université de Provence web site (www.up.univ-mrs.fr). The experimental titration data for glycinin were taken from (Thiering et al, 2001a). The theoretical titration curves for glycinin subunits, experimental titration curve for glycinin and isoelectric points of CR lipase isoenzymes are shown in Figure 3.…”
Section: Lipase and Glycinin Interactionmentioning
confidence: 99%
“…The use of volatile electrolytes in downstream processes of proteins is relatively recent with only a few reports in the open literature. The published studies on protein precipitation with volatile electrolytes were carried out with complex protein systems such as milk, soy protein extracts [5,6], and the fractionation of protein mixtures [7,8]. The isoelectric precipitation with carbon dioxide of a single protein, bovine serum albumin, was investigated by Qi et al [9]; additional investigations of the activity of some enzymes in the system formed by ethanol, carbon dioxide, and water were presented by Yao et al [10].…”
Section: Introductionmentioning
confidence: 99%
“…Tomasula et al (3)(4)(5) further investigated the process and explored promising applications in making improved casein sheets. Hofland et al (6) compared casein precipitation induced by CO 2 with conventional techniques with respect to yield and mineral partitioning using high-pressure pH measurements and then studied soybean protein in detail as well (7)(8)(9). All these suggested that CO 2 has many advantages over conventional precipitants such as mineral acids in isoelectric precipitation, and all the experiments above were carried out in aqueous solutions, where there are no residual organic solvents in the solution.…”
Section: Introductionmentioning
confidence: 99%